Response to orthodontic treatment with fixed appliances in adult patients compared to adolescents. A systematic review. - Guiñez, Marcial; Gabriela Letelier (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2022)
Objectives: This systematic review will seek to answer whether there are differences in the response to orthodontic treatment according to age, sex, and periodontal condition. Data Sources: A qualitative systematic review was carried out between 2016 and March 2021 in the electronic databases of PubMed, EBSCO Host, ClínicalKey, and BVS, selecting studies in English and Spanish with a maximum age of 5 years. The study was carried out according to the PRISMA statement. Data Selection: All the studies based on findings of orthodontic treatments in adult and adolescent human groups, healthy and/or with some conditions that may affect orthodontic treatment (periodontitis, postmenopausal) were included. Data Extraction: Study selection and data extraction were undertaken independently and in duplicate by two reviewers. There was a high degree of inter-examiner agreement for the eligibility assessment of the included articles (κ = 0.8637). Two reviewers assessed the quality of the included studies using AMSTAR-2, Cochrane’s RoB 2.0, ROBINS-I, and Tools for cross-sectional, case-control and case reports studies from The National Institutes of Health (NIH). Results: The search strategy used provided 1,350 papers of which 18 were selected for this study. Only 1 study showed a low risk of bias and 10 studies showed a high risk of bias. Adults show a late response after orthodontic activation. Periodontal conditions show improvement when periodontal and orthodontic treatment are combined. The response to orthodontic treatment does not show significant differences between adolescents and adults, or between premenopausal and postmenopausal women. Conclusions: The studies indicate that there is no difference in the response to orthodontic treatment according to age, sex, and periodontal condition, although there is great heterogeneity between the included studies and the majority present a high risk of bias, therefore the results must be carefully analyzed.